2012
DOI: 10.1007/s10396-012-0386-3
|View full text |Cite
|
Sign up to set email alerts
|

“Double eyes” sign of congenital bilateral dacryocystoceles

Abstract: Dacryocystocele is caused by nasolacrimal duct obstruction and results in cystic dilatation of the proximal part of the nasolacrimal duct, which is located inferomedial to the orbit, leading to fluid accumulation. It is important to consider that persistent congenital bilateral dacryocystoceles may cause neonatal nasal obstruction resulting in respiratory difficulty, and large dacryocystoceles may require surgical drainage. Ultrasonography demonstrates that congenital bilateral dacryocystoceles and normal eyeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Out of the 125 unilateral cases, 70 were right-sided, whereas 55 were leftsided. Seven of the studies reported 21 nonisolated cases including 15 major abnormalities such as central nervous system (CNS) anomalies, cardiac anomalies, renal anomalies, CDH, preaxial polydactyly, and six minor anomalies including mild ventriculomegaly, pyelectasis, and hypertelorism (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 125 unilateral cases, 70 were right-sided, whereas 55 were leftsided. Seven of the studies reported 21 nonisolated cases including 15 major abnormalities such as central nervous system (CNS) anomalies, cardiac anomalies, renal anomalies, CDH, preaxial polydactyly, and six minor anomalies including mild ventriculomegaly, pyelectasis, and hypertelorism (Table 2).…”
Section: Resultsmentioning
confidence: 99%